Epoxidation of Neral/Geranial using a Jacobsen-Katsuki Mn catalyst by chemical and electrochemical methods - Portilla Zúñiga, Omar Miguel (2016)
In this study, trans-(±)-N,N′-bis(salicylidene)-1,2cyclohexanediaminemanganese(III) chloride ([Mn(t-salcn)]Cl) was synthesized and used as a catalyst for the epoxidation of citral. The percentage of converted citral in two methods, chemical and electrochemical, was determined and compared; in the former method, the oxidizing agent NaClO was directly and completely added at the start of the reaction, while in the latter, ClO−was progressively generated in situ. The reaction was monitored by the quantification of citral using gas chromatography coupled to mass spectrometry. The results showed that in both cases, the major products correspond to epoxides from citral isomers, although differences were observed in the value of percentage of epoxides obtained, besides the generation of side reactions affecting the yield of the product of interest.